2021
DOI: 10.1039/d1ra01250a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible poly(vinylidene fluoride-co-hexafluoropropylene)-based gel polymer electrolyte for high-performance lithium-ion batteries

Abstract: Gel polymer electrolytes (GPEs) have attracted ever-increasing attention in Li-ion batteries, due to their great thermal stability and excellent electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…LMBs based on the PHGE-Li electrolyte showed the highest capacity retention rate of 92.3%, which was significantly higher than PLE (74.2%) and PGE-Li electrolytes (88.2%) and attributed to the higher IC and faster Li + transport of the PHGE-Li electrolyte. 36,61 The charge and discharge curves of LMBs under different cycles showed that LFP/PHGE-Li/Li had a lower polarization voltage (Figures 7c,d and S4a−d). In addition, electrochemical impedance spectroscopy (EIS, Figure S4e,f) also showed that the LFP/ PHGE-Li/Li battery had lower interfacial resistance, implying that PHGE-Li stably contacted the Li anode and had excellent interfacial compatibility.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…LMBs based on the PHGE-Li electrolyte showed the highest capacity retention rate of 92.3%, which was significantly higher than PLE (74.2%) and PGE-Li electrolytes (88.2%) and attributed to the higher IC and faster Li + transport of the PHGE-Li electrolyte. 36,61 The charge and discharge curves of LMBs under different cycles showed that LFP/PHGE-Li/Li had a lower polarization voltage (Figures 7c,d and S4a−d). In addition, electrochemical impedance spectroscopy (EIS, Figure S4e,f) also showed that the LFP/ PHGE-Li/Li battery had lower interfacial resistance, implying that PHGE-Li stably contacted the Li anode and had excellent interfacial compatibility.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…GPEs are usually prepared by immersing a porous polymer membrane in an LE. However, the intrinsic safety issues caused by LEs can be avoided by using gel and solid-type electrolytes [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PVDF-HFP has been blended with other molecules such as poly(ethylene oxide) (PEO), poly(methyl methacrylate) (PMMA), poly(vinyl acetate) (PVAc), poly(vinyl chloride) (PVC), thermoplastic polyurethane (TPU), poly(methyl methacrylate-co-acrylonitrile-co-lithium methacrylate) (PMAML), poly(ionic liquid), polysiloxane, and carboxymethyl cellulose (CMC). 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Here, it is notable that these polymer electrolytes have been developed for solid-state batteries (SSBs), which are one of the post-lithium-ion batteries (PLIBs) including sodium-ion batteries (SIBs), lithium-sulfur batteries (LSBs), and lithium-air batteries (LABs). [27][28][29][30][31][32] Specically, the peruoropolyether-based block copolymer electrolyte was designed for ultra-stable SIBs.…”
Section: Introductionmentioning
confidence: 99%